2020
DOI: 10.3892/mmr.2020.11592
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑145‑5p suppresses fascin to inhibit the invasion and migration of cervical carcinoma cells

Abstract: Micrornas (mirs) can affect the progression of cervical cancer (cc). The present study investigated the function of mir-145-5p in cc and demonstrated its association with fascin (FScn1). The expression levels of mir-145-5p in cc tissues and cell lines were analyzed using reverse transcription-quantitative Pcr, and its direct targets were explored using a luciferase reporter assay. The viability, migration and invasion of Hela cells transfected with small interfering FScn1 or with mir-145-5p mimics and inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
4
3
0
Order By: Relevance
“…Previous research has highlighted the dysregulation of miR-145-5p in various tumors, with evidence that it inhibits cancer development. [30][31][32] In our study, miR-145-5p expression was downregulated in NSCLC tissues, supporting earlier findings. 33 MiR-145-5p overexpression repressed cancer cell proliferation and metastasis, aligning with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous research has highlighted the dysregulation of miR-145-5p in various tumors, with evidence that it inhibits cancer development. [30][31][32] In our study, miR-145-5p expression was downregulated in NSCLC tissues, supporting earlier findings. 33 MiR-145-5p overexpression repressed cancer cell proliferation and metastasis, aligning with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…In line with this hypothesis, our results showed that circCPA4 bound to miR‐145‐5p to regulate NSCLC progression. Previous research has highlighted the dysregulation of miR‐145‐5p in various tumors, with evidence that it inhibits cancer development 30–32 . In our study, miR‐145‐5p expression was downregulated in NSCLC tissues, supporting earlier findings 33 .…”
Section: Discussionsupporting
confidence: 90%
“…The m6A methylation modification is not only reported to be involved in HPV infection but also closely related to the malignancies of cervical cancer, including migration, invasion and tumour infiltration 37–40 . Previous evidence showed that FSCN1 promotes cell proliferation, migration and invasion in ovarian cancer, non‐small cell lung cancer, colorectal cancer and cervical cancer 41–45 . This evidence supported our finding that FSCN1 was a downstream effector of the HPV‐m6A modification in CSCC, and upregulated the FSCN1 advanced cell proliferation, migration and tumorigenesis of CSCC.…”
Section: Discussionsupporting
confidence: 90%
“…MicroRNAs (miRNAs) are implicated in tumorigenesis by binding to the 3' UTR of target mRNA and repressing their translation. Diverse miRNAs can participate in CC development as tumor-suppressive miRNAs or oncomiRs [6][7][8][9]. For instance, miR-145-5p targets fascin to impede cancer cell migration and invasion in CC [6].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse miRNAs can participate in CC development as tumor-suppressive miRNAs or oncomiRs [6][7][8][9]. For instance, miR-145-5p targets fascin to impede cancer cell migration and invasion in CC [6]. Lysyl oxidase-like protein 2 (LOXL2) belongs to the lysine oxidase gene family and is crucial in catalyzing the formation of elastin and collagen cross-links in the extracellular matrix (ECM) [10].…”
Section: Introductionmentioning
confidence: 99%